The role of botulinum toxin type a-induced motor endplates after peripheral nerve repair - ERCAN, FERİHA; BAYRAMİÇLİ, MEHMET NURİ ÜMİT; ÖZKAN YENAL, NAZİYE; AKDENİZ DOĞAN, ZEYNEP DENİZ (WILEY, 2015)
Introduction: The aim of this study was to test the hypothesis that the increased number of new motor endplates induced by botulinum toxin type A (BTX-A) injection before nerve injury would be reinnervated after nerve repair, resulting in greater force generation. Methods: Thirty male Wistar rats were divided randomly into 3 groups: (1) controls; (2) a group with saline solution injection; and (3) a group with BTX-A injection into gastrocnemius muscle (BTX group). Thirty-six days after the injections the left sciatic nerve was divided and coapted in all groups. Eight weeks later, muscle forces were measured, and histological samples were collected. Results: No differences in the number of innervated endplates were found between the groups, but the number of denervated endplates was higher in the BTX group, as was the muscle tissue degeneration score. The BTX group showed distal muscle force measurements of up to 25.8% less compared with the control group. Conclusion: Although BTX-A injection increases the number of motor endplates, they are not functional. Muscle Nerve 52:412-418, 2015
Keywords: botulinum toxin; functional muscle transfer; motor endplate; muscle force-length curve; peripheral nerve repair; FUNCTIONAL MUSCLE TRANSFER; REINNERVATING AXONAL LOAD; SKELETAL-MUSCLE; NEUROMUSCULAR-JUNCTIONS; INTRACELLULAR CALCIUM; GROWTH; INJECTION; FORCE; MOUSE; INNERVATION